PENGARUH KEADILAN DISTRIBUTIF, KEADILAN PROSEDURAL, DAN KEADILAN INTERAKSIONAL TERHADAP KEPUASAN KERJA KARYAWAN - Dewi, Ida Ayu Anggia Wedya; Sudibya, I Gde Adnyana (E-Jurnal Manajemen; Vol 5 No 6 (2016), 2016)
This study was conducted to determine the effect of distributive justice, procedural justice, and interactional justice on employee job satisfaction at Batan Waru Restaurants Lippo Mall Kuta. The study was conducted on employees Batan Waru by the number of respondents as many as 35 employees. The number of respondents is determined using saturation sampling technique. The data collection is done by distributing questionnaires using a 5-point Likert scale to measure 26 indicators. Data analysis technique used is multiple linear regression. The test results distributive justice positive and significant impact on employee satisfaction, procedural fairness positive and significant impact on employee satisfaction, as well as interactional fairness positive and significant effect on employee satisfaction. The limitation of this study is the location of this research will be in the scope of the restaurant industry in Batan Waru Lippo Mall, Kuta, so the results of this study can not explain the circumstances of the other restaurants besides restaurants Batan Waru Lippo Mall, Kuta.
Keywords: Distributive Justice, Procedural Justice, Interactional Justice, Job Satisfaction